The Adaptation and Experience of Four Shoulder Patient-Centered Outcome Scores - Afsoun Nodehi Moghadam; Aylar Niknahad; Mahyar Salavati; Anoushirvan Kazem-Nezhad (University of Social Welfare and Rehabilitation Sciences, 2012)
Objective: The aim of this study was to achieve a reliable tool for measuring health related quality of life among Iranians with shoulder pain and disability. Materials & Methods: Through a non-experimental methodology study, four shoulder patient-centered outcome scores were translated and adapted culturally to Persian language. A total of 126 male and female patients with shoulder pain and disability were selected for examination of test -retest reliability of Iranian versions of shoulder outcome scores. The data was analyzed for evaluations of test -retest reliability, subscale and item internal consistency. Results: Internal consistency which was calculated by Cronbach &alpha was high for almost all the subscales (at least 0.7). Item internal consistency after correction for overlap was higher than optimal value (0.4), which demonstrated good item internal consistency. Test-retest reliability results showed that all the Persian versions of questioners' subscales had good reliability. Conclusion: With the preparation of Persian versions of shoulder pain and disability outcome scores ,some multidimensional instruments are available now to measure health status as well as therapeutic effects in patients with shoulder pain and disability.